Women in industry : North South connections (North-South Institute OttawaCA, 1985)
Discusses the impact of current trends in manufacturing production, investment and trade on women in the third world and Canada. Examines the roles and experiences of third world women in the textiles and clothing and electronics industries and discusses the effect of the expansion of developing country manufactured exports on Canadian women. Highlights employment alternatives for Canadian women and policy options in relation to women in both Canada and the developing countries. Discusses labour conditions in the third world and mechanisms for their improvement.
Bibliography:p. 70-75